Synthesis and Biological Evaluation of Metronidazole Derivatives as Anti-Giardia Agents - Bahador Shahriari; Zahra Rezaei; Soghra Khabnadideh; Hossein Sadeghpour; Gholam Reza Hatam; Qasem Asgari; Amin Kiani; Fardad Firoozi (Shiraz University of Medical Sciences, 2015)
Nitroimidazole derivatives such as Metronidazole (MTZ) have been used as anti- protozoa and anti-anaerobic bacteria. In this study several derivatives of MTZ were synthesized and evaluated against Giardia lamblia cyst. MTZ were reacted with several alkyl halide to obtain o-alkyl MTZ derivatives, then products were purified and their chemical structures were confirmed by spectral analysis (1HNMR and Mass). In order to assess biological evaluation, all compounds were investigated against 25 Giardia samples isolated from Giardia-infected patients. Results showed that compound 2 had the most activity on cyst of Giardia in comparison with MTZ.